2014
DOI: 10.17576/jsm-2014-4312-09
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Cations in Pickling Solution on FTIR Characteristics of Pidan White and Yolk in Comparison to the Fresh Duck Egg

Abstract: Fourier transform infrared (FTIR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The FTIR spectra matched those that Guo et al [47] found in the albumen of hen eggs. Additionally, it matched the duck albumen FTIR spectra reported by Ganezan et al [48] that were located in the amide band region, specifically amide I (1600-1700 cm −1 ), amide II (1500-1600 cm −1 ), amide III (1200-1300 cm −1 ), amide A (3293-3306 cm −1 ), and amide B (2920-2922 cm −1 ). It seems that salting with either brine or ozonized brine did not significantly chemically modify albumen proteins.…”
Section: Ftir Spectrasupporting
confidence: 87%
“…The FTIR spectra matched those that Guo et al [47] found in the albumen of hen eggs. Additionally, it matched the duck albumen FTIR spectra reported by Ganezan et al [48] that were located in the amide band region, specifically amide I (1600-1700 cm −1 ), amide II (1500-1600 cm −1 ), amide III (1200-1300 cm −1 ), amide A (3293-3306 cm −1 ), and amide B (2920-2922 cm −1 ). It seems that salting with either brine or ozonized brine did not significantly chemically modify albumen proteins.…”
Section: Ftir Spectrasupporting
confidence: 87%
“…6 A and B) of UDEP and SUDEP revealed that regardless of the ultrasound power or the addition of sodium pyrophosphate, the peak positions did not change significantly, no peaks disappeared, and no new peaks appeared, indicating that protein functional groups had not been entirely destroyed or generated under ultrasound or synergetic sodium pyrophosphate/ultrasound treatment. Among these peaks, with the increase of ultrasound power, the intensity of the hydroperoxide group (–OO-H) absorption peak (3442 cm −1 ) [37] of UDEP and SUDEP increased significantly, indicating that egg white protein might produce peroxide groups under ultrasonic treatment. These peroxide groups have the potential to oxidize sulfhydryl groups (to form disulfide bonds) and other groups to promote the crosslinking of protein.…”
Section: Resultsmentioning
confidence: 99%
“…Low temperature can reduce the loss of free alkali ions to a certain extent; hence, the rate of S1 decrease at low temperature was slower than that at normal temperature and high temperature. Because of the large amounts of sulfhydryl ( SH ) group and disulfide bond in proteins of preserved egg whites and the alkaline environment, the whole preserved egg white was negatively charged, and the repulsion between charges prompted the protein molecules to expand and expose their internal groups; hence, it can provide good conditions for SH oxidation and SH-SS exchange reaction ( Ganesan et al., 2014 , Zhao et al., 2016b ). At the same time, a decrease in pH during storage will reduce the electrostatic interaction and promote the formation of disulfide bonds ( Felix et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%